PENDATAAN KEPENDUDUKAN DI DESA SEDAPURKLAGEN KECAMATAN BENJENG SECARA OFFLINE MENGGUNAKAN APLIKASI POPULATION 3.0.0 SERTA PEMETAAN POTENSI DESA BULANGKULON - Effendi, Aris; Kurniasari, Lusiana; Ayu N., Riska Mulia; Nizar, Arif Abu; Nawa, Karlus (Jurnal Penamas Adi Buana, 2017)
Abstract The information system at the village level population data are usually still uses a manual system. This poses some obstacles are quite cumbersome, especially on invalidity and mismatch of data. Often occurs when the search constraints on information about new residents, or residents who moved out of the village. Similarly, the provision of data such as employment, education data, and demographic data of the population is often not up to date. Departing from the constraints above, then made the design of an information system on population. Expected population census information systems at the village level will greatly assist government agencies in conducting population census in the scope of a village. It where this system will make the process of data collection in line with the process of filing papers by each resident population that comes to the village office. Thus the population data can be obtained easily without having to collect data directly to where the people live. This system is designed with grooves and simple interface design, so that it can be easily used in rural environment, in this case taking the example Bulangkulon Village, subdistrict Benjeng, district Gresik. Key word :Information system, Data Collection, Population Abstrak Sistem informasi pada data populasi tingkat desa biasanya masih menggunakan sistem manual. Ini menimbulkan beberapa kendala yang cukup rumit, terutama pada cacat dan ketidaksesuaian data. Sering terjadi ketika kendala pencarian informasi tentang penduduk baru, atau penduduk yang pindah dari desa. Demikian pula, penyediaan data seperti pekerjaan, data yang pendidikan, dan data demografi penduduk sering tidak up to date. Berangkat dari kendala di atas, maka dibuat desain sistem informasi kependudukan. Diharapkan sistem informasi sensus penduduk di tingkat desa akan sangat membantu instansi pemerintah dalam melakukan sensus penduduk di lingkup desa. Hal mana sistem ini akan membuat proses pengumpulan data sejalan dengan proses kertas pengajuan oleh masing-masing populasi penduduk yang datang ke kantor desa. Dengan demikian data populasi dapat diperoleh dengan mudah tanpa harus mengumpulkan data langsung ke mana orang hidup. Sistem ini dirancang dengan alur dan desain antarmuka yang sederhana, sehingga dapat dengan mudah digunakan di lingkungan pedesaan, dalam hal ini mengambil contoh desa Bulangkulon, Kecamatan Benjeng, Kabupaten Gresik. Kata kunci: Sistem Informasi, Pendataan, Penduduk